2015
DOI: 10.1128/jvi.01238-15
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin-Neuraminidase Balance Influences the Virulence Phenotype of a Recombinant H5N3 Influenza A Virus Possessing a Polybasic HA 0 Cleavage Site

Abstract: Although a polybasic HA 0 cleavage site is considered the dominant virulence determinant for highly pathogenic avian influenza (HPAI) H5 and H7 viruses, naturally occurring virus isolates possessing a polybasic HA 0 cleavage site have been identified that are low pathogenic in chickens. In this study, we generated a reassortant H5N3 virus that possessed the hemagglutinin (HA) gene from H5N1 HPAI A/swan/Germany/R65/2006 and the remaining gene segments from low pathogenic A/chicken/British Columbia/CN0006/2004 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…[3][4][5] This functional balance between HA and NA is reected in the evolution of HA and NA. [6][7][8][9][10] It has therefore been suggested that all changes in activity of HA or NA must be followed by an adjustment of the activity of the other to maintain a functional balance. 6,7,11,12 In vivo studies have shown that lower NA activity leads to less efficient virus replication, but stronger binding by HA can have the same effect.…”
Section: P H (Erik) Hammingmentioning
confidence: 99%
“…[3][4][5] This functional balance between HA and NA is reected in the evolution of HA and NA. [6][7][8][9][10] It has therefore been suggested that all changes in activity of HA or NA must be followed by an adjustment of the activity of the other to maintain a functional balance. 6,7,11,12 In vivo studies have shown that lower NA activity leads to less efficient virus replication, but stronger binding by HA can have the same effect.…”
Section: P H (Erik) Hammingmentioning
confidence: 99%
“…This alteration results in HA cleavage-activation not only by tissue-restricted trypsin-like proteases that cleave LPAIV in the respiratory and digestive tracts, but also by ubiquitous furin-like proteases found throughout the host resulting in systemic infection6. Nevertheless, several H5 and H7 viruses with pCS exhibited relatively low virulence in chickens and further mutations within or beyond the HA were required for high virulence and/or efficient transmissibility in birds891011121314. To date little is known about the impact of different pCS sequences on virulence of AIV in chickens and modulation of virulence by the reassortment of different gene segments.…”
mentioning
confidence: 99%
“…Several attempts failed to convert an LP virus into the HP phenotype by merely grafting, by reverse genetics, a polybasic HACS into the HA protein of an LP H5 or H7 virus (Schrauwen et al., ; Stech et al., ). These investigations gave evidence that further, as yet ill‐defined, arrangements in either the HA or other viral proteins are required, at least in some viruses, in addition to a polybasic HACS (Abdelwhab et al., ; Diederich et al., ; Soda et al., ). Scattered throughout the genome of the currently studied LP/HP pair, ten amino acid substitutions outside the HACS were detected in the consensus sequence of the HPAI virus isolates, which allowed distinguishing the HP inheritor from its LP progenitor virus (Table ).…”
Section: Discussionmentioning
confidence: 99%